2019
DOI: 10.3233/atde190126
|View full text |Cite
|
Sign up to set email alerts
|

Product Platform: Trends and Opportunities

Abstract: Increasing market competitiveness forced industries to seek ways to reduce production costs and increase profitability. Companies operating in different markets face different customer expectations. Thus, it is necessary to develop products that meet the most varied market requirements, without demanding the high investment costs that product customization demands. The development of product platforms has helped companies to lower the cost of mass customization. The main benefit of using platforms is the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Both modularization and commonalization opt for reuse and flexibility, which may conflict with the integrative and static production-oriented design of DFA approaches [220]. This is backed up by the trends and opportunities of platform design identified by Cerqueira et al [226]. They argued that the consideration of joining elements is lacking and advocated for the creation assembly modules.…”
Section: State Of the Art Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both modularization and commonalization opt for reuse and flexibility, which may conflict with the integrative and static production-oriented design of DFA approaches [220]. This is backed up by the trends and opportunities of platform design identified by Cerqueira et al [226]. They argued that the consideration of joining elements is lacking and advocated for the creation assembly modules.…”
Section: State Of the Art Discussionmentioning
confidence: 99%
“…Schuh et al [225] argued that there are three generic objectives of modular platforms: reducing the time to market, reducing the costs, and managing the customer demand for variety. Cerqueira et al [226] analyzed the trends and opportunities of product platforms and identified three main problems, which are described as follows:…”
Section: State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations